2010
DOI: 10.2355/isijinternational.50.81
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal Behaviour by Its Injection into the Modern Blast Furnace

Abstract: Nowadays the use of charcoal in metallurgy is intimately linked to small blast furnaces in Brazil. Due to the challenge for CO 2 mitigation, interest for charcoal use as a renewable energy source is rising. In the scope of European efforts to mitigate carbon dioxide emissions in the steel industry in the post-Kyoto period, the use of charcoal in cokemaking and ironmaking has been investigated. This paper presents results of an experimental study on charcoal behaviour under the blast furnace simulating conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 8 publications
5
73
0
2
Order By: Relevance
“…This treatment for German oak's charcoal was performed because it was reported that the bark part contains relatively high amount of ash. 18) All of them were heated for 1 800 seconds under Ar flow at 1 273 K to remove volatile matter. After removing volatile matter, charcoal from Japanese oak was additionally heated for 1 800 seconds under Ar flow at 1 273 K, 1 773 K and 2 273 K to control the carbon crystallinity.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…This treatment for German oak's charcoal was performed because it was reported that the bark part contains relatively high amount of ash. 18) All of them were heated for 1 800 seconds under Ar flow at 1 273 K to remove volatile matter. After removing volatile matter, charcoal from Japanese oak was additionally heated for 1 800 seconds under Ar flow at 1 273 K, 1 773 K and 2 273 K to control the carbon crystallinity.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…O processo de injeção via ventaneiras dos altos-fornos (Pulverized Coal Injection -PCI) é bem estabelecido e flexível à incorporação de biomassa pulverizada em misturas com carvões. A injeção de finos de carvão vegetal, produzidos principalmente a partir de eucalipto, está consolidada nos chamados pequenos altos-fornos no Brasil, mas a injeção de biomassa em misturas com carvão em altosfornos a coque é um assunto recente [2,3]. A realização de um tratamento térmico com a madeira contribui na adequação de suas características químicas e físicas para um melhor aproveitamento como combustível/redutor no processo de injeção.…”
Section: Introductionunclassified
“…The by-products (coke gravel, coke sand and coke fines) from the coking plant would be high quality for use in reducing agent application. In Table 1, the chemical composition of coke gravel, coke sand and coke fines from Ruukki coking plant is compared to the composition of coke and two pulverized coals (PC) [10]. The total carbon of the PC 1 was 80.0% and PC 2 82.8%, respectively.…”
Section: Viscosity Measurement and Stability Of The Liquid-solid Mixturementioning
confidence: 99%